Effects of nasal instillation of a nitric oxide-releasing solution or parenteral administration of tilmicosin on the nasopharyngeal microbiota of beef feedlot cattle at high-risk of developing respiratory tract disease. (December 2017) - Timsit, E.; Workentine, M.; Crepieux, T.; Miller, C.; Regev-Shoshani, G.; Schaefer, A.; Alexander, T.
Abstract: Nitric oxide has bactericidal and virucidal properties. Nasal instillation of a nitric oxide releasing solution (NORS) on arrival at the feedlot was recently reported as inferior to a parenteral injection of tilmicosin (macrolide antibiotic) for control of bovine respiratory disease (BRD) in cattle at high-risk of developing BRD. We hypothesized that this inferiority was due to differences between treatments with regards to their effects on the nasopharyngeal microbiota. The objective was to compare nasal instillation of NORS versus parenteral administration of tilmicosin regarding their effects on the nasopharyngeal microbiota of feedlot cattle at high-risk of developing BRD. Culture-independent community profiling (16S rRNA sequencing) and culture-based methods were used to evaluate treatment effects. High-risk Angus-cross heifers (n = 20) were randomly allocated to 2 treatment groups on arrival at a feedlot and received either NORS or tilmicosin for prevention of BRD. Heifers were sampled using guarded deep nasal swabs immediately prior to treatment (day 0) and on days 1, 5 and 10 after treatment. Based on culture-independent community profiling, there was a distinct shift in composition of the nasopharyngeal microbiota during the first 10 d after arrival, with 116 OTUs changing over time, but no difference between treatment groups. However, culture-based methods detected a difference between treatment groups, with more cattle culture-positive for Pasteurellaceae in the NORS group at day 5 post-treatment. This difference in ability to inhibit colonization of the nasopharynx by Pasteurellaceae may be the basis for NORS being inferior to tilmicosin for control of BRD in high-risk cattle. Highlights: A nitric oxide releasing solution (NORS) has been developed for control of bovine respiratory disease (BRD). Effects on the nasopharyngeal microbiota of nasal instillation of NORS or parenteral tilmicosin were compared. No differences between treatment groups were observed based on 16S rRNA sequencing. However, more cattle were colonized with Pasteurellaceae in the NORS group based on culture. Difference in ability to inhibit colonization by Pasteurellaceae may explain inferiority of NORS compared to tilmicosin.